Research progress on mesenchymal stem cells and their exosomes in systemic sclerosis - Zhang, Yan; Yang, Yanli; Gao, Xiang; Gao, Wenqin; Zhang, Liyun (Frontiers in Pharmacology, 2023)
Systemic sclerosis (SSc) is a connective tissue disease with an unknown etiology. Clinically, it is characterized by localized or diffuse skin thickening and fibrosis. The pathogenesis of SSc includes microvascular injury, autoimmune-mediated inflammation, and fibroblast activation. These processes interact and contribute to the diverse clinicopathology and presentation of SSc. Given the limited effectiveness and substantial side effects of traditional treatments, the treatment strategy for SSc has several disadvantages. Mesenchymal stem cells (MSCs) are expected to serve as effective treatment options owing to their significant immunomodulatory, antifibrotic, and pro-angiogenic effects. Exosomes, secreted by MSCs via paracrine signaling, mirror the effect of MSCs as well as offer the benefit of targeted delivery, minimal immunogenicity, robust reparability, good safety and stability, and easy storage and transport. This enables them to circumvent the limitations of the MSCs. When using exosomes, it is crucial to consider preparation methods, quality standards, and suitable drug delivery systems, among other technical issues. Therefore, this review aims to summarize the latest research progress on MSCs and exosomes in SSc, offering novel ideas for treating SSc.